The changing forms of corruption in China - Bakken, Børge (Crime, law and social change, 2021)
China’s famed growth has created a paradox of huge proportions that is associated with how this development could happen despite the well documented issue of vast corruption. This growth has come through a specific form of corruption, changing from petty theft and speed money to grand theft and access money. The new forms of corruption were made possible through the access to assets like land, mines and State-Owned Enterprises (SOEs) after land-, property-, and SOE-reforms that were implemented during the 1990s. The opaque character of these reforms has led to what can only be described as a climate of grand collusion where officials use their access powers to redistribute what was formerly state-owned assets to themselves and crony entrepreneurs. While the character of corruption has changed over the last decade, the problem has not diminished despite continued official "anti-corruption" campaigns. The Chinese high growth/high corruption model has come with high risks growth and enormous inequality. Historically, Chinese dynasties have grown, decayed and fallen in scenarios similar to that of the present.